Eco-Green Catalys: An Intelligent Distribution Network for Generative Mycorrhizal Spores Through AI and Iot Optimization for Ecological Complexity Engineering in Post-Deforestation Lands Based on Restorative Bio-Economy Principles - Mahmudi, Gilang Arya; Lestari, Dwi Puji; Arianto, Davina Anindya Cindy (Journal of Regional Development and Technology Initiatives, 2026)
The ecological crisis caused by illegal deforestation has resulted in severe soil degradation, biodiversity loss, and disruption of ecosystem balance. Eco-Green Catalys emerges as an adaptive biotechnological innovation integrating Artificial Intelligence (AI) and the Internet of Things (IoT) to accelerate the restoration of post-deforestation lands. This system operates through an intelligent distribution network of generative mycorrhizal spores, which precisely controls inoculation, moisture regulation, and nutrient delivery based on real-time soil data analysis. Supported by a Spatio-Temporal Deep Learning (STDL-AI) framework, the system demonstrates up to 96% accuracy in ecological monitoring, enhances vegetation recovery rates by 70%, and increases carbon sequestration capacity by 35% compared to conventional restoration methods. Beyond ecological rehabilitation, this innovation reinforces the principles of restorative bio-economy by utilizing renewable energy sources and community-based participation, aligning with the Sustainable Development Goals (SDG 13) on climate action and long-term ecological resilience. Overall, Eco-Green Catalys provides a scalable and data-driven model that bridges environmental technology and socio-economic sustainability in restoring tropical ecosystems.